Evaluation of crop establishment methods and foliar nutrition for enhancing productivity of rice fallow/follow sesame (Sesamum indicum L.): EVALUATION OF ESTABLISHMENT METHODS AND FOLIAR NUTRITION FOR RICE FALLOW SESAME - C HARISUDAN; NISHA SAPRE (Journal of Oilseeds Research, 2019)
Field experiment to evaluate crop establishment methods and foliar nutrition for rice fallow/follow sesame (Sesamum indicum L.) was conducted for two consecutive years during rabi/summer 2015-16 and 2016-17 at TNAU, Regional Research Station, Vridhachalam under All India Coordinated Research Project on Sesame. The experiment was laid out in split plot design replicated thrice, with three crop establishment techniques in main plots and four foliar nutrition techniques in sub plots. Among the different crop establishment methods, sowing ofsesame after harvest of rice under till condition recorded higher final plant stand, maximumnumber of branches/plant (5.3), more number of capsules/plant (49) and maximum sesame seed yield (627 kg/ha). Similarly, sowing ofsesame after harvest of rice under till condition recorded maximum gross return (`51,828/ha), net return (` 29,653/ha) and B:C ratio (2.34). Poor crop stand and low yield was recorded under sowing 5 days before harvest of rice under moist condition. Among the foliar nutrition, combined foliar spray of 1% urea and 2% DAP at 35 DAS recorded more number of branches/plant (6.3) and capsules/plant (54) but it was on par with other foliar nutrition. The combined foliar spray of 1% urea and 2% DAP at 35 DAS showed its superiority by recording a maximum sesame seed yield (584 kg/ha), gross return (` 48,238/ha), net return (` 26,738/ha) and B:C ratio (2.24).